2017
DOI: 10.1021/acs.jced.7b00058
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Liquid–Liquid Equilibrium of Azeotropes (Water +2-Propanol) with Ionic Liquids ([Dmim][NTf2]) at Different Temperatures

Abstract: The liquid–liquid equilibrium (LLE) of a ternary system of water (H2O) + 2-propanol + 1-decyl-3-methylimidazolium bis­(trifluoromethylsulfonyl)­imide ([Dmim]­[NTf2]) ionic liquid was measured in the temperature range from 278.15 to 298.15 K at atmospheric pressure. The distribution coefficient and selectivity were calculated to determine the influence of the temperature on the LLE. The results indicate that a decrease in temperature reduces the solubility of H2O in [Dmim]­[NTf2] and increases the immiscibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…From Figures 5 and 6, as the temperature increases, the distribution coefficient and selectivity decrease slightly, Meanwhile, in Figures 1−4, as the solubility increases with the temperature increasing, the area of the heterogeneous region in the ternary phase diagrams decreased. Xu et al 27 explored the LLE for (water +2-Propanol + [Dmim][NTf 2 ]) at different temperatures. In their work, the experimental results indicate that two-phase region also decreased with the increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…From Figures 5 and 6, as the temperature increases, the distribution coefficient and selectivity decrease slightly, Meanwhile, in Figures 1−4, as the solubility increases with the temperature increasing, the area of the heterogeneous region in the ternary phase diagrams decreased. Xu et al 27 explored the LLE for (water +2-Propanol + [Dmim][NTf 2 ]) at different temperatures. In their work, the experimental results indicate that two-phase region also decreased with the increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…To recover IPA by liquid–liquid extraction, the extractant selection has been reported in some literatures, for instance, organic solvents, deep eutectic solvents, , and ionic liquids (ILs). ILs have been applied in the separation field due to their superiority in designability, thermal stability, and negligible vapor pressure. Cumplido et al performed the liquid–liquid equilibrium (LLE) exploration for the mixture water + IPA with different imidazolium-based ILs at temperatures of 283.2–323.2 K. All the used ILs played a positive role in recovering IPA from the azeotropic mixture. Liu et al determined the LLE behavior for water + IPA with the ILs 1-hexyl-3-methyl imidazolium bis­(trifluoromethylsulfonyl)­imide ([Hmim]­[NTf 2 ]), 1-octyl-3-methyl imidazolium bis­(trifluoromethylsulfonyl)­imide ([Omim]­[NTf 2 ]), and 1-decyl-3-methyl imidazolium bis­(trifluoromethylsulfonyl)­imide ([Dmim]­[NTf 2 ]) at 298.15 K. The results demonstrated that the ionic liquid with the longer alkyl chain length exhibited a strong ability to recover IPA.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al determined the LLE behavior for water + IPA with the ILs 1-hexyl-3-methyl imidazolium bis­(trifluoromethylsulfonyl)­imide ([Hmim]­[NTf 2 ]), 1-octyl-3-methyl imidazolium bis­(trifluoromethylsulfonyl)­imide ([Omim]­[NTf 2 ]), and 1-decyl-3-methyl imidazolium bis­(trifluoromethylsulfonyl)­imide ([Dmim]­[NTf 2 ]) at 298.15 K. The results demonstrated that the ionic liquid with the longer alkyl chain length exhibited a strong ability to recover IPA. The LLE behavior reported for the systems (water + IPA + [Dmim]­[NTf 2 ]) and (water + IPA + tetrabutylammonium dicyanamide) , revealed that the extraction capacity of the ILs decreased with increasing the temperature. Meanwhile, the pyridinium-based ILs have been used for the separation of cyclohexane, benzene, toluene, and nitrogen compounds and have shown good prospects in the applications of extraction processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Propanol is a basic chemical widely used in industry as a solvent or as a chemical intermediate because of its excellent physical and chemical properties. Separation of the aqueous mixture of 2-propanol is often demanded in its production and recovery, which is also conducive to environmental protection. The mixture of 2-propanol and water forms a minimum boiling point azeotrope at atmospheric pressure .…”
Section: Introductionmentioning
confidence: 99%